(untitled) (Bangladesh Journal of Agricultural Research, 2017)
An experiment was conducted in a venylhouse at the environmental stress site of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during September to December 2012 to study the effect of drought stress on proline content, soluble sugar content, chlorophyll content and cell membrane stability of soybean genotypes. Four studied genotypes viz., Shohag, BARI Soybean-6 and BD2331 (relatively stress tolerant) and BGM2026 (susceptible) were tested against two water regimes such as water stress and non-stress. Results indicated that due to drought stress there was an increase in proline content and soluble sugar content and decrease in chlorophyll a content, chlorophyll b content, total chlorophyll content, chlorophyll a/b ratio and cell membrane stability. Proline and soluble sugar showed more content in tolerant genotype than in susceptible ones. Chlorophyll reduction was most significant and cell membrane stability was found minimal in susceptible genotypes. From the result, genotype BGM2026 which recorded the lowest proline, soluble sugar content and highest chlorophyll reduction and cell membrane injury was considered as drought susceptible. The variety/genotype of soybean such as BARI Soybean-6, Shohag and BD2331 were more drought stress tolerant and better mechanisms of drought tolerance. Bangladesh J. Agril. Res. 42(3): 475-485, September 2017